Effects of endurance training on the relationship between blood glucose, lactate, and hormones during incremental running test - Nakamura, K.; Sengoku, Y.; Ogata, H.; Watanabe, K.; Shirai, Y.; Nabekura, Y. (International Journal of Sport & Health Science, 2020)
Aim: It has been reported that the relationships between blood glucose and lactate during incremental exercise has been affected by the training status. Nevertheless, the relationships between blood glucose, lactate, and hormones during incremental exercise in different training states have not been examined. Therefore, the purposes of this study were the examination of these relationships, and the evaluation whether these relationships were influenced by the training status. Methods: Eight male endurance runners (trained group) and eight active men (control group) participated in this study, and all participants participated in incremental running tests. Blood glucose, lactate, adrenaline, noradrenaline, and glucagon were evaluated at each stage during the incremental running test, and Spearman correlation coefficients between blood glucose, lactate, and hormones were calculated for each participant. The group differences in these data were evaluated using the Mann-Whitney U test. Results: The relationships between blood glucose and catecholamines were significantly stronger in the trained compared with the control group (p < 0.05). However, the relationships between blood lactate and catecholamines were not significantly different between groups. Furthermore, the relationships between glucagon and blood glucose or blood lactate did not differ significantly between groups, and these relationships were weak. Conclusions: We conclude that the increase in blood glucose may be influenced to a greater extent by catecholamines than by glucagon during incremental exercise. Furthermore, the relationships between blood glucose and catecholamines differed according to training status, and were different compared with the relationships between blood lactate and catecholamines.